PENGARUH PENIDIKAN ORANG TUA, PEMBELAJARAN DIPERGURUAN TINGGI DAN PENDAPATAN ORANG TUA TERHADAP LITERASI KEUANGAN (STUDI KASUS PADA STIE TRI DHARMA NUSANTARA MAKASSAR) - Makmur, Mariam; Taufiq, Muhammad; Yahya, Yahya (Paser Institute Of Accounting and Finance, 2024)
This study aims to analyze Parental Education, Higher Education Learning, and Parental Income Against Financial Literacy of STIE TRI DHARMA NUSANTARA Makassar Students. The population in this study were undergraduate students majoring in Management and Accounting who were active in the academic year until 2018 both male and female 2,838 students. This study uses the Slovin formula, so that a sample of 97 respondents is obtained. The analytical method used is multiple linear regression analysis using SPSS21 software. Based on multiple linear regression analysis in which the results, the variable of parental education is not significant to financial literacy, learning in higher education has a positive and significant effect on financial literacy and parental income is not significant to financial literacy.